Remaking academic library services in Zimbabwe in the wake of COVID-19 pandemic - Chisita, C.T.; Chiparausha, B.; Tsabetse, V.; Olugbara, C.T.; Letseka, M. (Elsevier, 2022)
The outbreak of the global COVID -19 pandemic has affected all aspects of life, access to higher education has not been out of danger as evidenced by the enforcement of official closures, enforcement lockdown and social distancing rules by governments throughout the world. However, while the COVID-19 pandemic has presented the world with numerous socioeconomic challenges, it has also helped to spur creativity and information as evidenced by the responses of academic libraries that have seen a heighted use of digital platforms to support education, teaching and research. The study sought to establish how librarians in Zimbabwe responded to the outbreak of COVID-19 and the implications of the pandemic on library service delivery. A qualitative research was adopted for the study. Using snowballing, interviews were used to gather data beginning with the library association's branch leadership. The researchers ensured that the questions were aligned to the research objectives. The interview schedule included open and closed questions to enable participants to provide further details relating to the phenomenon under study. The participants were guaranteed their rights to consent, privacy and anonymity in the introduction of the interview schedule. An The study reveals that there has been an increase in the use online platforms for accessing information especially library's webpages, electronic books and journals. The use of library online resources from distance locations also rose following closure of campuses. Library patrons' perceptions towards electronic resources significantly improved as they realized that they were equally useful as the print. Findings from the study provide useful recommendation on how librarians can remodel their services to match new demands presented by the COVD-19 pandemic. The study provides a starting point upon which further research on the effect of COVID-19 or other similar pandemics have on library service delivery.
Keywords: COVID-19; COVID; COVID-19 pandemic; academic libraries; digital technologies; access to information; Zimbabwe; digital divide